Extensive gain and loss of photosystem I subunits in chromerid algae, photosynthetic relatives of apicomplexans - Sobotka, Roman; Esson, Heather J; Koník, Peter; Trsková, Eliška; Moravcová, Lenka; Horák, Aleš; Dufková, Petra; Oborník, Miroslav (Scientific reports, 2017)
In oxygenic photosynthesis the initial photochemical processes are carried out by photosystem I (PSI) and II (PSII). Although subunit composition varies between cyanobacterial and plastid photosystems, the core structures of PSI and PSII are conserved throughout photosynthetic eukaryotes. So far, the photosynthetic complexes have been characterised in only a small number of organisms. We performed in silico and biochemical studies to explore the organization and evolution of the photosynthetic apparatus in the chromerids Chromera velia and Vitrella brassicaformis, autotrophic relatives of apicomplexans. We catalogued the presence and location of genes coding for conserved subunits of the photosystems as well as cytochrome b6f and ATP synthase in chromerids and other phototrophs and performed a phylogenetic analysis. We then characterised the photosynthetic complexes of Chromera and Vitrella using 2D gels combined with mass-spectrometry and further analysed the purified Chromera PSI. Our data suggest that the photosynthetic apparatus of chromerids underwent unique structural changes. Both photosystems (as well as cytochrome b6f and ATP synthase) lost several canonical subunits, while PSI gained one superoxide dismutase (Vitrella) or two superoxide dismutases and several unknown proteins (Chromera) as new regular subunits. We discuss these results in light of the extraordinarily efficient photosynthetic processes described in Chromera.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Thylakoids; superoxiddismutasa; fotosystém I (proteinový komplex); Phylogeny; Alveolata; fotosyntéza; Superoxide Dismutase; Photosynthesis; Gene Deletion; fylogeneze; tylakoidy; Evolution, Molecular; molekulární evoluce; delece genu; Photosystem I Protein Complex